Health problems in adolescent girls - Mendiratta, Suman Lata; Dath S., Suman; Yadav, Rekha; Mittal, Meenakshi; Naaz, Farah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Adolescents form precious human resources in every country, constitutes large number of populations. Adolescence is a period of rapid physical growth, sexual and psychological changes. The aim of the study is to assess the health problems in Adolescent girls and to take measures to prevent and treat their health problems. Methods: This prospective study was conducted from October 2014 to September 2016 in Hindu Rao hospital, North DMC medical college. Patients attending to gynecological outpatient department included in this study. The Statical analysis was done by using Microsoft excel. Results: Majority of patients in our study belongs to 15 to 19 years. Menstrual dysfunction (67.7%) is the most common complaint followed by leucorrhea (14.1%) and infections (10.6%). Conclusions: Adolescence girls presented with various gynaecological problems in our study. Setting up adolescent friendly clinics and privacy to discuss their problems is desirable for early diagnosis and management.